Peluang Dan Tantangan Kampus Merdeka Dalam Prespektif Pendidikan Agama Islam - Adona, Putri; Zakir, Supratman; Resya, Nolla; Nofrianti, Yerri (Ikhtisar: Jurnal Pengetahuan Islam, 2021)
An independent campus is a policy recently launched by the Indonesian minister of education, Nadiem Makarim. The independent campus policy is expected to be able to improve the quality of education in Indonesia, especially Islamic religious education, in the midst of the rapid development of information technology and the flow of globalization. A new policy or discourse is certainly an interesting topic to be discussed by both academics and practitioners. Furthermore, if it is associated with Islamic education, the concept of independent learning is not a taboo subject. Because basically the Qur'an and Hadith have discussed this concept of free learning. So the purpose of this paper is to reveal the opportunities and challenges of an independent campus in the perspective of Islamic religious education. The method that the author uses is a literature study, by digging up information about the topic of discussion from various existing literature and then analyzing it. In the results of the study, information was obtained that the opportunities for the existence of this independent campus program were as research development, entrepreneurial development, and adaptive graduates. Meanwhile, the challenge is the collaboration mechanism between private Islamic universities and study programs with outside parties and the internship mechanism outside the study program.